The subaortic tendon as a mimic of hypertrophic cardiomyopathy - Ker James (Cardiovascular Ultrasound, 2009)
Abstract Originally described by Brock and Teare, today hypertrophic cardiomyopathy is clinically defined as left (or right) ventricular hypertrophy without a known cardiac or systemic cause, such as systemic hypertension, Fabry's disease or aortic stenosis. Also appreciated today is the enormous genotypic and phenotypic heterogeneity of this disease with more than 300 mutations over more than 24 genes, encoding various sarcomeric, mitochondrial and calcium-handling proteins, all as genetic causes for hypertrophic cardiomyopathy. Phenotypically, the disease can vary from negligible to extreme hypertrophy, affecting either the left and/or right ventricle in an apical, midventricular or subaortic location. Left ventricular false tendons are thin, fibrous or fibromuscular structures that traverse the left ventricular cavity. Recently, a case report was presented where it was shown that such a false tendon, originating from a subaortic location, was responsible for striking ST-segment elevation on the surface electrocardiogram. In this case report, a case is presented where such a subaortic tendon led to the classic echocardiographic appearance of hypertrophic cardiomyopathy, thus in the assessment of hypertrophic cardiomyopathy, this entity needs to be excluded in order to prevent a false positive diagnosis of hypertrophic cardiomyopathy.